Pemodelan Arsitektur Enterprise Sistem Informasi Rencana Kerja dan Anggaran Rumah Sakit dengan Zachman Framework - Putra, Rona (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Raden Mattaher Jambi Regional General Hospital is required to submit a Work Plan and Budget every period. The preparation of the RKA report starts from collecting proposals from each work unit to the approval process by the Board of Directors on the proposals of each work unit. In an effort to streamline business processes that occur, analyze data needs, processes and also actors involved in organizational activities, an Information System is needed to streamline processes that occur, collect all required data and create proposal reports. In addition, to unravel the complexity of the processes that occur, a framework is needed that can be used as a guide and reference in modeling the organization's business processes. This study uses the Zachman Framework as a reference framework that includes what, how and who columns and rows in the perspective of planners, owners and designers. From the results of the analysis carried out with the Zachman Framework, then the information system architecture modeling is carried out by utilizing tools in the form of flowmaps, use cases and class diagrams. With modeling that is designed to be a reference for developing information systems and unraveling the complexity of the process and knowing the parties involved and the required system interfaces.